Effect of torsion on externally prestressed segmented box bridge girder - Al-Gorafi, Mohammed Abdulla Ismail (2011)
Externally Prestressed Segmented (EPS) concrete box bridges are widely used in the construction of bridge structures today. EPS has also become an attractive tool for rehabilitation and strengthening of existing structures with insufficient strength and/or excessive deflection and cracking. The behaviour of externally prestressed segmented bridge has been studied under either shear force or combined bending moment and shear forces only. No extensive research work has been carried out so far to study the effect of combined bending, shear force,normal force and torsion on the structural behaviour of these bridges. Therefore, there is a need to focus on this area; and hence, both analytical and experimental investigation need to be carried out to study the behaviour of EPS box bridge under combined bending, shear, normal force and torsion. The key objective of the research was to obtain a better understanding of the behaviour of externally prestressed segmented box bridge girders under combined loading, and to study the significance of torsion in the overall response. The research was also intended to study the effect of joint opening on the overall response of the bridge. In addition, this research aims at proposing a formula to estimate the failure load of EPS bridge girders under combined loading, since no design code provides a formula to estimate the load capacity of EPS bridges under such loading condition. The scope of this study was limited to determining deformation characteristics, strain variation, onset point of nonlinearity load, failure load and failure mechanism. The effect of different parameters studied include joint type (flat and with shear key) and tendon layout (harp and straight). There were three different load cases: without torsion, and with torsion imposed by different load eccentricities. To achieve these objectives, 12 specimens of externally prestressed segmented box bridge girders were tested. In addition, Finite Element (FE) analysis was conducted on a some of these girders using ANSYS finite element package. Three different types of elements (cube element, interface element and link element) were used in the FE analyses. Both geometric and contact nonlinearities were incorporated. The result of adopted Finite Element analysis was verified twice, once with the result of real bridge (in Bangkok), and another with the results of adopted experiments. So, the result of FE shown that the FE modelling can be used to simulated. This research was conducted for a better understanding of the behaviour of externally prestressed segmented bridges under combined loading. The results indicated that torsion has a significant effect on EPS bridges. Torsion not only reduces the value of failure load but also affects the failure mechanism. It was concluded that the contact nonlinearity due to joint opening affected the behaviour of EPS bridges. Finally, aformula was proposed to estimate the failure load of EPS beams.